Instrumentalization of the symbolic artifact 1st degree equations with two unknowns in a non-digital environment (Research, Society and Development, 2022)
This article aims to analyse the process of instrumentalization of the symbolic artifact 1st degree equation with two unknowns in 8th grade elementary school students. The theoretical framework used was the Instrumentation Theory from the perspective of Pierre Rabardel. With a qualitative approach and an action-research design, the data were collected from observation, audio and video recordings and material produced by the students. Recognizing that the graphic representation of a 1st degree linear equation with two unknowns is a straight line in the Cartesian plane is the main objective of an instrumentalization process of this mathematical object and constitutes the starting point of the phenomenon of Instrumental Genesis. From the observations took, it was possible to point the groups realized that, even though each one has constructed rectangles of different dimensions, what evidently resulted in tables with different values, the algebraic expression to represent the regularity observed in the tables was the same, diverging only in the letters chosen by each group to represent the rectangle dimensions. Moreover, the groups realized their graphic representations diverged only in the chosen points but it was the same line, thus demonstrating the instrumentalization process of the present mathematic object.